The Attractive Serratia plymuthica BMA1 Strain With High Rock Phosphate-Solubilizing Activity and Its Effect on the Growth and Phosphorus Uptake by Vicia faba L. Plants. Issue 5 (11th April 2020) - Borgi, Mohamed Ali; Saidi, Issam; Moula, Amel; Rhimi, Sofien; Rhimi, Moez
Abstract: The present work aims to investigate the attractive ability of the newly isolated bacterium Serratia plymuthica BMA1, to release phosphorus (P) from rock phosphate (RP) and also to assess its beneficial effect in promoting the growth of Vicia faba . This strain exhibited the highest RP-solubilization activity ever reported, with 450 mg l −1 of soluble P at 30 °C. At 10 and 20 °C, its RP-solubilization was estimated at 100 and 200 mg l −1, respectively. HPLC analysis revealed that RP-solubilizing activity was associated with the release of gluconic acid. The hydroxyapatite (HA) solubilization activity concomitantly occurred with the secretion of gluconic acid and lactic acid. Under greenhouse conditions, application of BMA1 strain as an inoculant in presence of RP as the sole P source, considerably increased phosphorus uptake by V. faba L. and upgraded its overall growth in terms of dry weight and length by 76% and 39%, respectively. This growth promoting effect was accompanied by a substantial increase in chlorophyll contents. Additionally, phosphorus levels within roots and shoots of S. plymuthica BMA1-treated plants were approximately three times greater, compared to the non-inoculated control plants. When HA was used instead of RP, bacterization with BMA1 strain also enhanced the plant growth parameters and P contents, but significantly less than RP. These findings revealed that S. plymuthica BMA1 could be a potential candidate to improve the agronomic effectiveness of RP, toward a clean P-nutrition through the formulation of bio-phosphate fertilizers for plant growth promotion.